2016
DOI: 10.1373/clinchem.2015.249706
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells: A Review of Non–EpCAM-Based Approaches for Cell Enrichment and Isolation

Abstract: International audienceBackground: Circulating tumor cells (CTCs) are biomarkers for non-invasively measuring the evolution of tumor genotypes during treatment and disease progression. Recent technical progress has made it possible to detect and characterize CTCs at the single-cell level in blood. Content: Most current methods are based on epithelial cell adhesion molecule (EpCAM) detection, but numerous studies have demonstrated that EpCAM is not a universal marker for CTC detection since it fails to detect bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
200
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(203 citation statements)
references
References 71 publications
1
200
0
2
Order By: Relevance
“…Examples of commercial tests based on negative depletionRosetteSep. [11] Finally, CTC detection and characterization can be done by immunocytological (flow cytometry); molecular (reverse transcription-polymerase chain reaction [RT-PCR]); and functional assays (cell culture -EPISPOT; xenotransplantation).…”
Section: Methods For Circulating Tumor Cells Isolation and Detectionmentioning
confidence: 99%
“…Examples of commercial tests based on negative depletionRosetteSep. [11] Finally, CTC detection and characterization can be done by immunocytological (flow cytometry); molecular (reverse transcription-polymerase chain reaction [RT-PCR]); and functional assays (cell culture -EPISPOT; xenotransplantation).…”
Section: Methods For Circulating Tumor Cells Isolation and Detectionmentioning
confidence: 99%
“…Alternative marker-independent methods are based on physical properties of CTCs for discrimination from blood cells such as size, rigidity, surface charge, flow characteristics and others. [19] These techniques result in detection of larger numbers of CTCs compared to the CellSearch© system and the additional cells found may be more aggressive and invasive than EpCAM-positive cancer cells. The multitude of methods to capture CTCs are described in a large number of comprehensive reviews.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…size, density and electric charge) or biological (e.g. surface protein expression and invasive capacity) properties have been developed [70]. The only system approved by the United States Food and Drug Administration (US FDA) for enrichment and enumeration of CTCs is the CellSearch ® system, which enriches isolated CTCs by using magnetic bead-conjugated antibodies against epithelial-cell adhesion molecules (EpCAM) in 7.5 mL of blood [70].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…surface protein expression and invasive capacity) properties have been developed [70]. The only system approved by the United States Food and Drug Administration (US FDA) for enrichment and enumeration of CTCs is the CellSearch ® system, which enriches isolated CTCs by using magnetic bead-conjugated antibodies against epithelial-cell adhesion molecules (EpCAM) in 7.5 mL of blood [70]. However, a large body of evidence has demonstrated that EpCAMs is not universal makers for isolating CTCs, especially for those CTCs that have undergone epithelial-mesenchymal transition or have originated from the mesenchymal [70].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%